Association of blood mercury levels with nonmelanoma skin cancer in the U.S.A. using National Health and Nutrition Examination Survey data (2003–2016). (1st September 2020) - Rhee, J.; Vance, T.M.; Lim, R.; Christiani, D.C.; Qureshi, A.A.; Cho, E.
Summary: Background: Some studies have reported increased incidence or mortality of lung and brain cancers associated with occupations involving potential mercury exposure. Epidemiological evidence related to skin cancer is also limited. Objectives: To investigate the association between blood mercury (Hg) levels and nonmelanoma skin cancer (NMSC). Methods: We used National Health and Nutrition Examination Survey data from 2003 to 2016. The exposures were blood total (tHg), inorganic (iHg) and methylmercury (MeHg). The outcome was a self‐reported diagnosis of NMSC. We included participants aged ≥ 20 years who had information on blood mercury and sociodemographic factors. We conducted a logistic regression analysis to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for the risk of NMSC associated with quartiles of blood Hg, after adjusting for the sociodemographic factors and survey year. Results: The number of participants was 29 413; mean age was 49 years and 52% were female. Compared with those with a tHg ≤ 0·47 μg L −1 (Q1), those with a tHg > 1·74 μg L −1 (Q4) had nearly double the odds of NMSC (OR 1·79, 95% CI 1·19–2·71; P trend = 0·004). Similarly, those in the highest quartile of MeHg (> 1·44 μg L −1 ) had 1·7 times greater odds of NMSC (OR 1·74, 95% CI 1·13–2·70; P trend = 0·01) than those in the lowest quartile (≤ 0·21 μg L −1 ). iHg levels were nonsignificantly positively associated with NMSC ( P trend = 0·08). Conclusions: We found that higher blood tHg and MeHg levels were associated with a higher prevalence of NMSC. Linked Comment:  Taylor. Br J Dermatol 2020; 183 :413–414 .